Pengaruh Pembelajaran Field Project Terhadap Peningkatan Kemampuan Berpikir Kreatif Dan Inovatif Dalam Buku Ajar Kewirausahaan Untuk Mahasiswa Universitas Hamzanwadi Tahun 2025 - Rohaeniyah Zain; Susilawati Susilawati; Agus Riswanto; Asti Maulina; Yuliana Safitri; Suzila Iin Rohmatin (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
This study aims to analyze the effect of Field Project-based learning on improving students’ creative and innovative thinking skills through entrepreneurship textbooks at Universitas Hamzanwadi. This research employed a quantitative approach using a quasi-experimental one-group pretest–posttest design involving 40 students enrolled in entrepreneurship courses. Data were collected using validated creative and innovative thinking tests and analyzed using descriptive statistics, paired sample t-test, and N-gain analysis. The results show that the average pretest score increased from 62.4 to 81.7 in the posttest. The paired sample t-test result indicates t = 9.86 with p < 0.05. The N-gain value of 0.63 falls into the moderate-to-high category. These findings indicate that Field Project-based learning is effective in enhancing students’ creative and innovative thinking skills and supports learning outcomes aligned with the Merdeka Belajar–Kampus Merdeka (MBKM) policy and higher education Key Performance Indicators (IKU).